Production Process Monitoring System for RFID-Based SMEs and the Internet of Things - Sipurba, Iguh; Widya Sari, Marti; Hardyanto, R. Hafid; Harry Pratisto, Eko (Lembaga Penelitian dan Pengabdian Mayarakat (LPPM) Universitas PGRI Yogyakarta, 2023)
Micro, Small, and Medium Enterprises (UMKM ) illustrates business being run either by private, home households, as well as business entities size small. this venture's own role is important in the growth and industry of a country. In these global economic times, In this case, MSMEs are demanded to carry out replacement To use upgrade energy it's competitive. One aspect that means what you want to ensure energy MSME competitiveness is technology information ( IT ). Adana Sugar Ants